2010
DOI: 10.1016/j.jus.2010.06.002
|View full text |Cite
|
Sign up to set email alerts
|

Contrast-enhanced US evaluation in patients with blunt abdominal trauma

Abstract: KEYWORDSUltrasonography; Contrast agent; Abdominal trauma.Abstract Introduction: To evaluate the use of contrast-enhanced ultrasonography (CEUS) in patients with blunt abdominal trauma. Materials and methods: A total of 133 hemodynamically stable patients were evaluated using ultrasonography (US), CEUS and multislice Computer Tomography (CT) da eliminare. Results: In 133 patients, CT identified 84 lesions: 48 cases of splenic injury, 21 of liver injury, 13 of kidney or adrenal gland injury and 2 of pancreatic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
39
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(39 citation statements)
references
References 25 publications
0
39
0
Order By: Relevance
“…It has been argued that CEUS can be considered in the triage of hemodynamically stable children with blunt abdominal trauma [18]. Several studies applying CEUS in blunt abdominal trauma in adults have shown similar results with CEUS outperforming conventional US and comparable to the performance of contrast-enhanced CT [27][28][29][30]. It is in agreement with these findings that CEUS could supersede contrast-enhanced CT in the follow-up of trauma and become the main imaging modality in traumas of minor or moderate severity.…”
Section: Parenchymal Injuries In Blunt Abdominal Traumamentioning
confidence: 62%
“…It has been argued that CEUS can be considered in the triage of hemodynamically stable children with blunt abdominal trauma [18]. Several studies applying CEUS in blunt abdominal trauma in adults have shown similar results with CEUS outperforming conventional US and comparable to the performance of contrast-enhanced CT [27][28][29][30]. It is in agreement with these findings that CEUS could supersede contrast-enhanced CT in the follow-up of trauma and become the main imaging modality in traumas of minor or moderate severity.…”
Section: Parenchymal Injuries In Blunt Abdominal Traumamentioning
confidence: 62%
“…42 CEUS can be considered as first-line imaging in centers where ultrasound is part of the initial trauma screening protocol. 43,44 More importantly, it is especially useful for serial monitoring for conservatively managed patients without exposing them to further radiation. 41…”
Section: Ultrasoundmentioning
confidence: 99%
“…The use of CEUS signifi cantly increases the sensitivity in detecting the parenchymal lesions, and perirenal hematoma, even if very small [ 9 ].…”
Section: Us-ceusmentioning
confidence: 99%
“…In the follow-up, US allows to evaluate the possible development of pancreatic pseudocysts and/or abscesses and to monitor its progress [ 9 ].…”
Section: Usmentioning
confidence: 99%
See 1 more Smart Citation